Amongst Green Revolution?: A Study of Hunger and Under-Nutrition in Punjab. - Sharma, Pawan Kumar and Bhatia, Manisha (2012)
An attempt is made here to understand the state of affairs pertaining to hunger and under-nutrition in the green revolution State of Punjab. The basic hypothesis is that such a state should be free from this malady. Indicators used for the purpose are incidence of low weight, thinness and stunting among children and body mass index level among adults. Micronutrient deficiencies including anaemia across different segments of population have also been examined along with impact of public sector initiatives to check the menace of hunger and under-nutrition. Secondary data from a various sources including NFHS, DLHS, NNMB, NSSO and from the records of different government departments has been put in service. The state figured disappointingly on this count, defying the hypothesis postulated. One-fourth of children were found as underweight and one-eighth of adults had BMI below the normal levels. No less than 80 per cent of the children, 33 per cent of the women and 40 per cent of the pregnant women suffered from anaemia. Consumption of lower levels of proteins and micronutrients continue to persist among different segments of population. It is ironical that despite the fact that the green revolution has improved productivity, availability and access of food in the State there has not been a commensurate decrease in the levels of hunger and under-nutrition; not to mention other states where agriculture is still to make headway. The impact of a variety of strategies undertaken by the State Government to meet the situation has been quite feeble. The state needs to strengthen its efforts to fight against endemic hunger and under-nutrition. Efforts to ensure availability of food must be combined with care for health, particularly for tackling the prevalence of anaemia in general.